(untitled) (FULafia Journal of Science and Technology, 2020)
Fifty non-composited well cutting samples from a depth range of 486 – 3216 m of the BIMOL-1 well located in the north-western area of the Niger Delta Basin, were subjected to palynological and lithofacies analyses for the purpose of zonation and paleo depositional environment interpretation. Forty two miospore and ten dinocyst species were identified and used to age-date the sediments as Ypresian – Rupelian in age. Occurrence and abundance of age-significant species enabled four non-formal assemblage zones equivalent to existing palynological zones (P300 – P560) of the Niger Delta Basin to be erected. A subdivision of the extant P420 zone that spans the Upper Ypresian – Lower Lutetian into a lower and an upper subzone with the Ypresian – Lutetian boundary as the boundary of the two new subzones A and B was done, which will enable a finer scale well-well and field-wide correlation in the BIMOL-1 well area